Comparison of efficiency, security and stability between RouterOS from MikroTik and Cisco IOS, in network engineering environments (Revista Científica Interdisciplinaria Investigación y Saberes, 2024)
The comparative study between Cisco and MikroTik devices for internet service providers (ISPs) in Ecuador sought to evaluate the efficiency, security and stability of MikroTik's RouterOS and Cisco IOS operating systems in network environments. A methodology combining theoretical and exploratory analysis was employed, using data from the ISP company "JEAPC". Aspects such as geography, static and dynamic routing, IP address translation, Google Cache network segregation and bandwidth limitation were evaluated. JEAPC" was found to have a robust data transfer capacity, serving 2800 customers, mainly in the Triunfo-Troncal region. Significant differences were identified between Cisco and MikroTik devices. For example, the Cisco ASR920 showed routing versatility, but lacked IP address translation and bandwidth limitation features for individual clients. In contrast, the MikroTik CCR2004-16G stood out for its routing stability, IP address translation capability and bandwidth limitation at the client level, being scalable and efficient for medium-sized environments. The findings highlighted the importance of considering current needs and future scalability when choosing between MikroTik and Cisco devices. MikroTik was identified as an efficient solution, especially beneficial for businesses with tight budgets and moderate growth, while Cisco was positioned as a solid choice for businesses with ambitions for expansion. The right choice will depend on the long-term strategy of each ISP in Ecuador